Written corrective feedback in English compositions: Teachers’ practices and students’ expectations - Wan Noor Miza Wan Mohd Yunus (Universitas Ahmad Dahlan, 2020)
Written corrective feedback (WCF) has been the subject of many studies in the field of second language (L2) writing. This study sought to investigate: (1) teacher’s practices in marking students’ English language compositions, (2) students’ expectations of teacher’s WCF, and (3) compare whether students’ expectations correspond to teachers’ practices of WCF. Sixty-four students and three teachers of an upper secondary school in Malacca, Malaysia participated in this study. Teachers’ WCF practices and students’ preferences were elicited from two different sets of questionnaires. Findings revealed that both students and teachers generally believe that WCF is beneficial in improving students’ writing skills. It was also discovered that students prefer direct, specific, and comprehensive feedback over indirect feedback. However, the study showed some discrepancies between students’ preferences and teachers’ practices in composition classrooms in terms of the amount, type, and necessity of the feedback where most students were found to require more WCF than the amount their teacher was capable of giving. This misalignment calls for teachers’ and students’ adjustments to ensure the effectiveness of WCF strategies employed by teachers. Findings from this research also imply that the study of contextual factors and beliefs influencing preferences with regard to WCF may also be necessary.